Etika Permaculture Sebagai Solusi Ilmiah Untuk Keberlanjutan Lingkungan dan Ekonomi yang Meredakan Kecemasan Petani Organik - Kusnaedi, Putri Maudi; Hartono, Choirussahla Aqiilah; Kamilah, Shofiah; Ernah, Ernah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Environmental damage, particularly in the field of agriculture, remains a hot topic of national discourse. On the other hand, human demands for natural resources and agriculture are on the rise in tandem with population growth. In response to these circumstances, a new paradigm for the development of environmentally friendly and sustainable agricultural systems and lifestyles has emerged in Indonesia, known as permaculture, which embodies ethical principles. The objective of this research is to examine how the ethics of permaculture can serve as a scientific solution to environmental and economic sustainability, aiming to alleviate concerns among organic farmers. The research is conducted at Kebun Hanif Regenerative Culture in West Bandung Regency. This study employs a qualitative descriptive method. The research findings indicate that the application of permaculture ethics in Kebun Hanif demonstrates commendable environmental sustainability, as evidenced by various indicators such as soil physical, biological, and chemical properties, which signify fertile soil. Economic sustainability through the application of permaculture ethics is also deemed viable based on a business feasibility analysis. Consequently, farmer anxieties have diminished because, by adopting permaculture ethics, not only is environmental sustainability achieved, but economic viability and sustainability are also proven.